IMPLEMENTASI MANAJEMEN KESISWAAN DALAM PENGUATAN BUDAYA DAN KARAKTER ISLAMI DI MADRASAH - Sutopo, Hadi; Suyatno; Santosa, Achadi Budi (Irfani, 2026)
Strengthening Islamic culture and character has become an urgent need in Islamic primary education amid the challenges of moral degradation and declining student discipline. Madrasahs, as value-based educational institutions, play a strategic role in nurturing noble character through structured and sustainable guidance. One crucial instrument in this process is student management, which includes planning, organizing, implementing habituation programs, and supervising students’ behavior in an integrated manner. This study aims to analyze the implementation of student management in strengthening Islamic culture and character at Madrasah Ibtidaiyah Al-Islamiyah, Ukui District, Pelalawan Regency, Riau. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that student management plays a significant role in shaping a religious and orderly madrasah culture. Habituation programs such as the recitation of asmaul husna, dhuha prayer, BTQ and tahfiz, muhadarah, and congregational prayers are effective in fostering discipline, politeness, self-confidence, and students’ spiritual attachment to the Qur’an. This study offers an implementative model of student management based on Islamic habituation that is systematic and sustainable